Modern Educational Technologies in the Aspect of A Student-Centered Approach in Teaching Foreign Languages - Dilorom Tasheva; Nafisa Kubaeva (Genius Journals, 2022)
One of the main tasks of teaching the foreign language is not only to give knowledge to students, but also to awaken a personal motive, instill interest in the subject, develop a desire for speech self-improvement. In this regard, in the modern methodology, the goals of education are specified, the content and structure of education are changed. Accordingly, the forms of training are being improved, the methods and techniques of training are being specified. The purpose of the article is the study of new pedagogical technologies in the teaching of the foreign languages, their impact on the quality of education
Keywords: Training; reportage; differentiation; method